2003
DOI: 10.1053/jlts.2002.50014
|View full text |Cite
|
Sign up to set email alerts
|

Are cytokine gene polymorphisms related to in vitro cytokine production profiles?

Abstract: Currently, there is much interest in the genetic basis for diseases or disease manifestations and, in particular, in whether they are related to cytokine gene polymorphisms. It has become accepted to denote such single‐nucleotide polymorphisms of cytokine genes by their presumed association with high or low in vitro cytokine production. In this article, we analyze the relationship between cytokine gene polymorphisms and in vitro tumor necrosis factor alpha (TNFα), interferon gamma (IFNγ), and interleukin (IL)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 41 publications
3
79
1
2
Order By: Relevance
“…However, in general, our results are in line with most previous studies suggesting an increased IL-10 production with rs1800896G and a decreased IL-10 production with rs1800871T and rs1800872A, [13][14][15][16][17][18][19][20][21][22] although there are also studies reporting on opposite results. [23][24][25] Taking into account the 2-year interval between measurements and the field conditions in which samples were collected and the stimulation assay was performed, we consider the repeated measurements to correlate well, especially for IL-10. This provides evidence that the strength of the IL-10 response of an individual is relatively stable over time in a pathogen-rich environment, suggesting an important role for genetics in the production of IL-10 even under high infectious pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, our results are in line with most previous studies suggesting an increased IL-10 production with rs1800896G and a decreased IL-10 production with rs1800871T and rs1800872A, [13][14][15][16][17][18][19][20][21][22] although there are also studies reporting on opposite results. [23][24][25] Taking into account the 2-year interval between measurements and the field conditions in which samples were collected and the stimulation assay was performed, we consider the repeated measurements to correlate well, especially for IL-10. This provides evidence that the strength of the IL-10 response of an individual is relatively stable over time in a pathogen-rich environment, suggesting an important role for genetics in the production of IL-10 even under high infectious pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between genotype and phenotype cannot always be clearly demonstrated. 25 PE and E are considered as expressions of the same syndrome, with E being the most severe form of PE. Although other studies have investigated the relationship between PE and cytokine gene polymorphism, few have evaluated eclamptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following the kit's manufacturer's suggestion and literature recommendations, [23][24][25] cytokine genotype and phenotype were grouped as follows: for the TNF-a gene, the alleles were distributed as A/A and A/G (high) and G/G (low); for the IL-6 gene, the groups were G/G and G/C (high) and C/C (low); for the IL-10 gene, the alleles for each polymorphism were grouped as GCC/GCC (high), GCC/ATA and GCC/ACC (intermediate) and ACC/ACC and ACC/ATA (low); for the IFN-g gene, the alleles were distributed as T/T (high), T/A (intermediate) and A/A (low); and for the TGF-b1 gene, the groups were T/T G/G and T/C G/G (high), T/C G/C and C/C G/G (intermediate) and C/C G/C, C/C C/C, T/T C/C and T/C C/C (low).…”
Section: Methodsmentioning
confidence: 99%
“…Using a number of different assays, several groups investigated the effect of STR and SNP ( þ 874) polymorphisms on IFN-gamma production (reviewed by Warle et al 4 and Vanderbroeck and Goris 5 ). It was generally found that individuals homozygous for STR allele 2 (or having T at polymorphic position þ 874), in contrast to those carrying allele 3 (or þ 874 A), had a greater IFN-gamma secretion by peripheral blood mononuclear cells (PBMC) upon different mitogen stimulations.…”
mentioning
confidence: 99%